Core environment program and biodiversity conservation corridors initiative in the Greater Mekong Subregion (Asian Development Bank, 2011)
Contents: The core environment program (CEP-BCI); Environmental assessments of economic corridors and sectors; Biodiversity conservation corridors intiative (BCI)...